2016
DOI: 10.1002/tox.22335
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to PM2.5 causes genetic changes in fetal rat cerebral cortex and hippocampus

Abstract: PM travels along the respiratory tract and enters systemic blood circulation. Studies have shown that PM increases the incidence of various diseases not only in adults but also in newborn infants. It causes chronic inflammation in pregnant women and retards fetal development. In this study, pregnant rats were exposed to PM for extended periods of time and it was found that PM exposure increased immune cells in mother rats. In addition, cytokines and free radicals rapidly accumulated in the amniotic fluid and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 88 publications
2
26
0
Order By: Relevance
“…According to the American Environmental Protection Administration (EPA) (2015), the major air pollutants include NO x , SO 2 , O 3 , PM 2.5 , and PM 10 . PM 2.5 refers to fine particles with an aerodynamic diameter less than or equal to 2.5 μm [ 1 ]. It consists of complex constituents including heavy metals and toxic organic pollutants, and there are several investigations concerning the effects of exposure to air pollutants on admission rates, mortality rates and prognosis of respiratory diseases, cardiovascular disease, and stroke [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the American Environmental Protection Administration (EPA) (2015), the major air pollutants include NO x , SO 2 , O 3 , PM 2.5 , and PM 10 . PM 2.5 refers to fine particles with an aerodynamic diameter less than or equal to 2.5 μm [ 1 ]. It consists of complex constituents including heavy metals and toxic organic pollutants, and there are several investigations concerning the effects of exposure to air pollutants on admission rates, mortality rates and prognosis of respiratory diseases, cardiovascular disease, and stroke [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal mice exposed to secondary organic particles demonstrated a decrease in social behaviour with down-regulation of estrogen receptor-β and oxytocin receptor in the hypothalamus [173]. Ming-Wei Chao et al reported an increase in reactive oxygen species and several cytokines in the amniotic fluid, and changes in microRNA expression profile in the cerebral cortex and hippocampus of foetal brains in rats following exposure to PM 2.5 [174].…”
Section: Main Textmentioning
confidence: 99%
“…One of the biological mechanisms by which air pollutants may affect brain is through neuroinflammation (Allen et al, 2013). Exposure to PM 2.5 causes chronic inflammation in pregnant women, along with retarded fetal development and genetic changes in fetal hippocampus (Chao et al, 2017). Our results showed that the exposure led to activation of microglia and astrocytes, along with enhanced GFAP-labeled astrocytes and Iba1-labeled microglia in CA1, CA3, and DG regions, suggesting the activation of neuroglial cells in these hippocampal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollutants are complex mixtures containing particles, gasses, adsorbed metals and organic pollutants. PM 2.5 (aerodynamic diameters equal to or less than 2.5 μm) acts as a major type of air pollutants and can absorb large quantities of heavy metals and toxic organic pollutants (Chao et al, 2017). Environmental exposure to PM 2.5 results in about 42 million deaths, accounting for approximately 7.6% of the total number of deaths worldwide (Cohen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%